Critica sociale e individuazione - Spinosi, Nicola (Strumenti per la didattica e la ricerca, 2004)
The process of individuation (according to Jung) aims to free us from what is not for us, to strip us of encrustations, of fashions. However, this process should not be the prerogative of the development of the person: it should instead extend, as a model, to the development of socio-cultural criticism, in the sense that we should be able to identify the characteristics of each collective phenomenon. By paying attention to the suggestions offered by the news, politics, social psychology, fiction, and cinema, the texts collected in this volume make up this project - articulating identification with social criticism - to try and throw off the shackles that prevent us from being in front of new and strange facts without comparing them and referring to old, usual, habitual, obvious facts.